Employability skill among engineering graduate in Malaysia / Nurul Aqila and Noraini Nordin - Nurul Aqila, Nurul Aqila; Nordin, Noraini (Universiti Teknologi MARA, Kedah, 2019)
Acquiring suitable skills to be employ along with knowledge of science and mathematics. However, the workplace has changed by globalization and most engineers need to work in a multi-disciplinary environment. This paper would like to look forward of engineering employability skills by comparing few countries which are Malaysia, Japan, India, United State and Singapore. There few several employability skills were point out and acquire for an engineer which are communication skills, teamwork skill, problem solving skill and interdependent skills. This study also not only beneficial for graduates and higher education as references to develop academia curriculum but also develop graduate employability skill in their self in obtain job.